Perancangan Sistem Informasi Kawasan Wisata Mandeh Berbasis Web dengan Pendekatan User-Centered Design - Azmi, Luxfy Roya; Ramadhani, Salisa ‘Asyarina; Putri, Vivin Mahat; Azhar, Wafianda (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
The Mandeh Tourism Area, located in Pesisir Selatan Regency, West Sumatra, is a leading destination with significant potential in the marine tourism sector. Often referred to as the